2012
DOI: 10.1007/s10529-012-1084-3
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2, VEGF and bFGF synergistically promote the osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) were treated with bone morphogenetic protein-2 (BMP-2), vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) dose-dependently and time-dependently. Together they caused a strong synergistic effect on the osteogenic differentiation of MSCs, with lower concentrations of each factor being enough to show the synergistic promotion (50 ng BMP-2/ml, 1 ng VEGF/ml and 10 ng bFGF/ml). When both VEGF and bFGF were added in the early proliferating stage (the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…BMP‐2 receptors have been reported to co‐localize or overlap with integrin in osteoblasts, and BMP‐2 activity was found to be closely associated with the function of αvβ integrins . The presence of RGD enhanced the effects of BMP‐2 in promoting the expression of osteocalcin and osteopontin as well as stimulating the synthesis of other growth factors, including VEGF and IGF . Changes in gene and protein expression modulate the function of the MSCs and ultimately lead to the differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP‐2 receptors have been reported to co‐localize or overlap with integrin in osteoblasts, and BMP‐2 activity was found to be closely associated with the function of αvβ integrins . The presence of RGD enhanced the effects of BMP‐2 in promoting the expression of osteocalcin and osteopontin as well as stimulating the synthesis of other growth factors, including VEGF and IGF . Changes in gene and protein expression modulate the function of the MSCs and ultimately lead to the differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…63 The presence of RGD enhanced the effects of BMP-2 in promoting the expression of osteocalcin and osteopontin as well as stimulating the synthesis of other growth factors, including VEGF and IGF. 64 Changes in gene and protein expression modulate the function of the MSCs and ultimately lead to the differentiation of MSCs. He et al 65 also demonstrated that RGD and BMP peptides, when grafted onto a hydrogel substrate, act synergistically to promote osteogenic differentiation and mineralization of MSCs.…”
Section: Synergistic Effects Of Rgd and Bmp-2mentioning
confidence: 99%
“…The process is influenced by the presence of different proteins, hormones and growth factors. Bone morphogenetic protein (BMP) is the classic osteogenic protein,11 and Liu et al 12 have elucidated the exact mechanism by which BMP affects MSCs. This protein generates the transcription factor Smads by combining with type I or II serine/threonine receptor on the MSC membrane to activate 203 gene loci which control the osteoblast differentiation of MSCs.…”
Section: Influences On the Differentiation Of Mscsmentioning
confidence: 99%
“…Mesoporous material loading of bioactive proteins has been used for bone repair in recent years [19,21,[24][25][26][27][28][29] where the complicated microenvironment of the human body has to be considered for MHA, especially different pH values. The pH of the normal extracellular fluid is about 7.4, while the osteoclast establishes an acidic micro-environment between itself and the bone wherein matrix degradation occurs by a process involving proton transport [30].…”
Section: Introductionmentioning
confidence: 99%